Estudo cefalométrico longitudinal (em média, 6 anos e 2 meses pós-tratamento) das alterações tegumentares ocorridas em adolescentes tratados com e sem extrações dentárias - Itaborahy, Wanderson Márcio (2007)
The results showed that, as years had gone by, a significant and gradual growth of the nose and the chin occurred, as well as a relative stability in the anteroposterior ratio of the lips. However, there was a retrusion of the lips in relation to the line “S”, as a result of the nasal and menton growth, resulting in a gradual reduction of the convex face, and altering the proportion of the tissue profile, as time had gone by. Those alterations were observed in both groups, from the beginning to the end of the treatment – from the final to the 6 years and 2 months post-treatment, and also from the beginning to the 6 years and 2 months post-treatment (total time of assessment), except for the group without extractions, where the alterations in the chin and in the “S” line inferior lip (S-Li) were not significant, just from the initial to the final treatment. When the groups were compared, it was observed a increase of the nasal prominence, as well as the menton projection, and a reduction of the “S” line inferior lip (S-Li) greater in the group treated with extractions, from the beginning to the end of the treatment. Besides, it was observed a increase of the nasal prominence and a reduction of the “S” line inferior lip (S-Li) greater in the group treated with extractions, but only from the beginning to the 6 years and 2 months post treatment (total time of assessment). It was emphasized the importance of the appearance approach in the orthodontic procedure, and it was suggested, as a clinical conduct of precaution, to finish off the case with the lips more exserted in relation to the line “S” of Steiner, with the objective of keeping the proportion of the facial profile in future.